RETRACTED: Non-intertwined strands of plasmid DNA contradict the Watson and Crick model of DNA structure [version 3; peer review: 1 approved, 1 approved with reservations, 1 not approved] - Pawan Kumar (F1000Research, 2022)
At the request of the author, the article titled “ Non-intertwined strands of plasmid DNA contradict the Watson and Crick model of DNA structure ” [version 3; peer review: 1 approved, 1 approved with reservations, 1 not approved]. F1000Research 2020, 8:356 ( https://doi.org/10.12688/f1000research.18134.3 ) has been retracted from F1000Research. Previous versions of this article published on F1000Research have also been retracted ( https://doi.org/10.12688/f1000research.18134.1 ; https://doi.org/10.12688/f1000research.18134.2 ). Since publication, Dr Pawan Kumar has performed additional experiments on the structure of a DNA molecule and was not able to generate further results that support this article. As such, they are no longer confident in the conclusions drawn in this article, and wish to retract. They apologise for any inconvenience caused